2021
DOI: 10.1016/j.jsxm.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction After Pelvic Fracture: A Comprehensive Review of the Literature

Abstract: Background Female sexual dysfunction (FSD) after pelvic fracture (PFx) has garnered little attention in the urology literature. Aim To review and summarize the current evidence regarding female PFx-related sexual function. Methods We performed a systematic review in accordance with PRISMA guidelines, including PubMed, EMBASE, and MEDLINE. We included only Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Prior studies have suggested increased rates of C-section, SD, and GD after pelvic fractures. 3 4 5 6 7 8 , 10 - 12 However, these studies have key limitations, such as small sample size and reliance on questionnaires. A clearer picture of the long-term effect of pelvic fracture on these outcomes is crucial and may allow orthopaedic surgeons to better counsel patients with these injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have suggested increased rates of C-section, SD, and GD after pelvic fractures. 3 4 5 6 7 8 , 10 - 12 However, these studies have key limitations, such as small sample size and reliance on questionnaires. A clearer picture of the long-term effect of pelvic fracture on these outcomes is crucial and may allow orthopaedic surgeons to better counsel patients with these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pelvic fractures have been associated with persistent symptoms of sexual dysfunction (SD) 4 , 10 - 12 and genitourinary dysfunction (GD), 4 , 7 which likely arise from concomitant injury to nearby soft-tissue and key nervous, reproductive, and urinary structures. However, because many of these studies assess dysfunction with questionnaires instead of confirmed diagnosis, reliance on data from patient self-reporting and nonvalidated questionnaires may cause survey and measurement bias.…”
mentioning
confidence: 99%
“…When compared to wrist fractures, hip or thigh fractures and pelvic fractures were the only major traumas included in this study that had a negative impact on the birth rate during the five subsequent years after sustaining the fracture. There are a few studies that have reported sexual dysfunction in women with proximal thigh traumas or pelvic traumas, with sexual dysfunction occurring mostly among younger women [13,14]. However, a study on proximal thigh traumas reported that in most cases only a few women report anything other than mild or no sexual dysfunction after 1-year follow-up [14].…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies have focused mainly on trauma and abnormalities of the reproductive system, especially of the uterus and ovaries [12]. It has been reported, however, that musculoskeletal trauma around the area of the pelvic ring and the femur can cause sexual dysfunction and dyspareunia [13,14]. Moreover, women in Finland who have undergone total hip replacement are reported to have a lower birth rate than women in the general population [15].…”
Section: Introductionmentioning
confidence: 99%
“…Johnsen et al 46,47 have explored barriers to care of sexual health concerns in men after traumatic pelvic fractures, with the most common issues identified as a lack of discussion with their healthcare provider after injury combined with the belief that sexual dysfunction would resolve with time, plus the perceived lack of value and importance placed on sexual health as a component of survivorship. Similarly, a recent systematic review by Walton et al 48 identified female sexual dysfunction as an underrecognized sequela of pelvic fracture, noting that future prospective studies need to better characterize sexual dysfunction and, most importantly, identify effective treatments for female sexual health in trauma survivors. Together, this would indicate that patient counseling and timing of interventions as it relates to urinary and sexual disabilities needs to be different, and that early involvement of multidisciplinary experts is important.…”
Section: Discussionmentioning
confidence: 99%